Antibiotic use in neonatal sepsis - Yurdakök, Murat (The Turkish Journal of Pediatrics, 1998)
Neonatal sepsis is a life-threatening emergency and any delay in treatment may cause death. Initial signs of neonatal sepsis are slight and nonspecific. Therefore, in suspected sepsis, two or three days empirical antibiotic therapy should begin immediately after cultures have been obtained without awaiting the results. Antibiotics should be reevaluated when the results of the cultures and susceptibility tests are available. If the cultures are negative and the clinical findings are well, antibiotics should be stopped. Because of the nonspecific nature of neonatal sepsis, especially in small preterm infants, physicians continue antibiotics once started. If a baby has pneumonia or what appears to be sepsis, antibiotics should not be stopped, although cultures are negative. The duration of therapy depends on the initial response to the appropriate antibiotics but should be 10 to 14 days in most infants with sepsis and minimal or absent focal infection. In infants who developed sepsis during the first week of life, empirical therapy must cover group B streptococci, Enterobacteriaceae (especially E. coli) and Listeria monocytogenes. Penicillin or ampicillin plus an aminoglycoside is usually effective against all these organisms. Initial empirical antibiotic therapy for infants who developed sepsis beyond the first days of life must cover the organisms associated with early-onset sepsis as well as hospital-acquired pathogens such as staphylococci, enterococci and Pseudomonas aeruginosa. Penicillin or ampicillin and an aminoglycoside combination may also be used in the initial therapy of late-onset sepsis as in cases with early-onset sepsis. In nosocomial infections, netilmicin or amikacin should be preferred. In cases showing increased risk of staphylococcal infection (e.g. presence of vascular catheter) or Pseudomonas infection (e.g. presence of typical skin lesions), antistaphylococcal or anti-Pseudomonas agents may be preferred in the initial empirical therapy. In some centers, third-generation cephalosporins in combination with penicillin or ampicillin have been used in the initial therapy of early-onset and late-onset neonatal sepsis. Third-generation cephalosporin may also be combined with an aminoglycoside in places where aminoglycoside-resistance to this antibiotic is high. However, third-generation cephalosporins should not be used in the initial therapy of suspected sepsis, because 1) extensive use of cephalosporins for initial therapy of neonatal sepsis may lead to the emergence of drug-resistant microorganisms (this has occurred more rapidly as compared with the aminoglycosides), 2) Antagonistic interactions have been demonstrated when the other beta-lactam antibiotics (e.g. penicillins) were combined with cephalosporins. Infections due to gram-negative bacilli can be treated with the combination of a penicillin-derivative (ampicillin or extended-spectrum penicillins) and an aminoglycoside. Third-generation cephalosporins in combination with an aminoglycoside or an extended-spectrum penicillin have been used in the treatment of sepsis due to these organisms. Piperacillin and azlocillin are the most active of extended-spectrum penicillins against Pseudomonas aeruginosa. Among the third-generation cephalosporins, cefoperazone and ceftazidime possess anti-Pseudomonas activity. Ceftazidime was found to be more active in vitro against Pseudomonas than cefoperazone or piperacillin. New antibiotics for gram-negative bacteria resistant to other agents are carbapenems, aztreonam, quinolones and isepamicin. Enterococci can be treated with a cell wall-active agent (e.g. penicillin, ampicillin, or vancomycin) and an aminoglycoside. Staphylococci are susceptible to penicillinase-resistant penicillins (e.g. oxacillin, nafcillin and methicillin). Resistant strains are uniformly sensitive to vancomycin. A penicillin or vancomycin and an aminoglycoside combination result in a more rapid bacteriocidal effect than is produced by either drug alone.